(3GdQhV GdHGSe aj MhGOK GdYeQ hGdJQGLes - (3YHO GdHGSW Hf Ndjd Hf TGgjf GdedWj, Ke GdbGgQj, Rjf GdOjf,J (B920 (3g` s
(3ChdgG (B:s
(3HYO JcedI GdJQLeI GdhGQOI ai BNQ GdLRA GdKGfi JQLeI YeQ Hf GdHHGfi GdcQOi fRjd GdbGgQI s
(3BNQgG (B:s
(3hef fhGOQgG cKQI GdYeGFQ hGdCHfjI GdJi CfTCgG hedcgG CjVkG GdJi bd Cf hbYJ Ch de JbY dedc bHdg hGdJYdbGJ GdJi JNJU Yed GdhRQGA hGdGSJGOGQGJ s
(3ef HbjI hajGJ SfI (B868 - (3SfI (B872(3g`s
(3HgG fXGe GdJYbjHI s
(3HChdgG agQS HNW MOjK HebOGQ KeGfi hQbGJs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs